PEMANFAATAN TANAMAN GULMA KAYAMBANG (Salvinia Molesta) SEBAGAI BAHAN PAKAN AYAM BURAS MELALUI ENERGI METABOLISMENYA - Sindu Akhadiarto (Jurnal Rekayasa Lingkungan)
Kayambang is water seed from Indonesia which can be used for animal feed. In village it is usually used for duck and village fowl (kampong chicken). Kayambang grows very much on water surface and have hight nutrition include energy and protein. Animal feed are used for growth requirement and to support sintetics reactionsform its body. Energy from the feed is not used for animal infull. In each ingredient at least has 4 kind of energy : Gross Energy, Digestible energy, Metobalic energy and netto energy. Metabolic energy is impotant to measure form each ingredient because it is used for all requirement such as maintanance, growth, feedlot and layer. This research has goal for knowing about metabolic energy which can be used for animal especially for village fowl.The methodology was done by 14 male village fowl (11 chicken for metabolic energy, 3 chicken for endogenous nitrogen). Individual was caged to collect feces. Kayambang was used as meal and given to the chicken. The results showed that Kayambang has energy contains potentially for village fowl. Total metabolic energy is 2857,56 and apparent metabolic energy is 2433,66 Kkal/kg.Key words : kayambang, village fowl, animal feed, nutrition.